2019
DOI: 10.24252/eternal.v52.2019.a12
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Vocabulary Mastery Through Word-Connection Game

Abstract: Many students face difficulties to express their mind, ideas and feelings because lack of vocabulary. This fact makes them loose the point of information and lead them to the thought that English is a difficult subject, till even frustration. This is why every student must master vocabulary, because when they do, it will be easy for them to master the four language skills. This reasearch aimed to find (1) whether the use of Word-Connection game significantly improved the students vocabulary mastery of the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…While doing the activity students seemed enjoyed and fun and it showed that they could remember the words provided easily. Same as the result of the research that showed the students were excited and motivated during the activity of the komunikata game and it proved that this game can improve students' vocabulary mastery (Tanasy and Ali, 2019). And next the teacher 3 applied cross word puzzle game to teach vocabulary to her students.…”
Section: Strategies Used By the Teachers To Promote Active English Le...mentioning
confidence: 88%
“…While doing the activity students seemed enjoyed and fun and it showed that they could remember the words provided easily. Same as the result of the research that showed the students were excited and motivated during the activity of the komunikata game and it proved that this game can improve students' vocabulary mastery (Tanasy and Ali, 2019). And next the teacher 3 applied cross word puzzle game to teach vocabulary to her students.…”
Section: Strategies Used By the Teachers To Promote Active English Le...mentioning
confidence: 88%
“…EFL learners can significantly utilize many electronic media, such as computers and mobile phones, to improve their vocabulary (Ansarin et al, 2017;Har et al, 2019;Rahman & Angraeni, 2020). It is supported by various types of digital games that can be used to teach vocabulary (Lube & Nuraeni, 2020;Tanasy, 2019;Wu et al, 2020). However, if used too often, digital games can interfere with physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this hypothesis of Stephen Krashen states that more input will reach the LAD and language acquisition will be achieved if we are at ease and experience a welcoming learning atmosphere. This was also supported by the the concept which explains that giving students interactive activities promote, opportunity to work independently or in group, teamwork, to become more active and collaborative in their learning experiences, and to take control of what they are learning [14].…”
Section: Part II Test Of Difference Between the Pretest And Posttest ...mentioning
confidence: 98%